In silico and in vitro evaluation of two novel oximes (K378 and K727) in comparison to K-27 and pralidoxime against paraoxon-ethyl intoxication. (2nd January 2018) - Arshad, Maria; Fatmi, Muhammad Qaiser; Musilek, Kamil; Hussain, Alamdar; Kuca, Kamil; Petroianu, Georg; Kalasz, Huba; Nurulain, Syed Muhammad
Abstract: Organophosphate (OP) poisoning is a major global health issue; while compounds from this group have been used intensively over the last century, an effective antidote is still lacking. Oxime-type acetylcholinesterase (AChE) reactivators are used to reactivate the OP inhibited AChE. Pralidoxime is the only US Food and Drug Administration approved oxime for therapeutic use but its efficacy has been disappointing. Two novel oximes (K378 and K727) were investigated in silico and in vitro and compared with an experimental oxime (kamiloxime; K-27) and pralidoxime. In silico the molecular interactions between AChE and oximes were examined and binding energies were assessed. LogP (predicted log of the octanol/water partition coefficient) was estimated. In vitro the intrinsic ability of the oximes to inhibit AChE (IC50 ) and their reactivation potency ( R 50 ) when used in paraoxon inhibited human RBC-AChE was determined. Molecular docking revealed that K378 and K727 bind to the peripheral site(s) with high binding energies in contrast to the central binding of K-27 and pralidoxime. LogP values indicating that the novel compounds are significantly less hydrophilic than K-27 or pralidoxime. IC50 of K378 and K727 were comparable (0.9 and 1 µM, respectively) but orders of magnitude lower than comparators. R 50 values revealed their inability to reactivate paraoxon inhibited AChE. It is concluded that the novel oximes K378 and K727 are unlikely to be clinically useful. The in silico and in vitro studies described allow avoidance of unnecessary in vivo animal work and contribute to the reduction of laboratory animal use.